A descriptive analysis of real-world treatment patterns of innovator (Remicade®) and biosimilar infliximab in an infliximab-naïve Turkish population - Yazici Y (Dove Medical Press, 2018)
Yusuf Yazici,1 Lin Xie,2 Adesuwa Ogbomo,2 Lorie A Ellis,3 Kavitha Goyal,4 Amanda Teeple,5 Ece A Mutlu,6 Ismail Simsek7 1Department of Internal Medicine, Division of Rheumatology, New York University Hospital for Joint Diseases, New York, NY, USA; 2STATinMED Research, Health Economics and Outcomes Research, Ann Arbor, MI, USA; 3Janssen Scientific Affairs, Real World Value and Evidence, Titusville, NJ, USA; 4Janssen Biotech Incorporated, Immunology Medical Affairs, Horsham, PA USA; 5Jassen Scientific Affairs, LLC, Health Economics and Outcomes Research, Horsham, PA, USA; 6Rush University, Medical College, Department of Medicine, Chicago, IL, USA; 7Guven Hospital, Department of Rheumatology, Ankara, Turkey Purpose: Biosimilar IFX (CT-P13) received marketing approval in Turkey for treatment of rheumatologic diseases, including ankylosing spondylitis, psoriatic arthritis, rheumatoid arthritis (RA), inflammatory bowel disease (IBD), and psoriasis. Population data on real-world treatment patterns of CT-P13 following marketing approval in European countries are largely unreported. This study examined the prescribing and medication utilization patterns of innovator infliximab (IFX) and CT-P13 in Turkey for patients with RA or IBD naïve to either IFX.Materials and methods: Adult patients with ≥1 diagnosis claim for RA or IBD and ≥1 claim for IFX or CT-P13 were identified in the Turkish Ministry of Health database during the following identification periods: 1 Oct 2014–30 May 2015 (RA) and 1 Oct 2014–31 Dec 2015 (IBD). Continuous medical and pharmacy coverage for ≥12 months before and after the date of the first dose (index) IFX or CT-P13 was also required. Separate analyses were done for each population.Results: Seven hundred and seventy nine adult RA and 581 IBD patients met the selection criteria. The majority of RA (74%; n=575) and IBD patients (87%; n=504) were initiated on IFX. The average study observation period was 16 months for the RA and 12 months for the IBD population. Over the observation periods, discontinuation among RA patients occurred in 42% of IFX and 63% of CT-P13 while discontinuation in the IBD cohort occurred in 38% of IFX; and 62% of CT-P13.Conclusion: In this population-based study, more IFX-naïve RA and IBD patients were initially treated with IFX than CT-P13. Discontinuation and switching were observed more often and earlier among patients treated with CT-P13 regardless of disease state. Further studies are needed to understand the reasons for these observed differences. Keywords: discontinuation, switch, inflammatory bowel disease, rheumatoid arthritis